Healthy play, better coping: The importance of play for the development of children in health and disease. (December 2018) - Nijhof, Sanne L.; Vinkers, Christiaan H.; van Geelen, Stefan M.; Duijff, Sasja N.; Achterberg, E.J. Marijke; van der Net, Janjaap; Veltkamp, Remco C.; Grootenhuis, Martha A.; van de Putte, Elise M.; Hillegers, Manon H.J.; van der Brug, Anneke W.; Wierenga, Corette J.; et al.
Highlights: "Rodent studies support an important role of social play in the development of brain and behavior". "Children with a chronic disease are at risk for physical, social, emotional and cognitive problems". "Facilitating (social) play may improve the developmental outcome of chronical diseased children". "All children may benefit from knowledge about the impressive resilience of young patients". "Interactive technology/games can help patients to play with peers, fostering social inclusion". Abstract: Play is of vital importance for the healthy development of children. From a developmental perspective, play offers ample physical, emotional, cognitive, and social benefits. It allows children and adolescents to develop motor skills, experiment with their (social) behavioural repertoire, simulate alternative scenarios, and address the various positive and negative consequences of their behaviour in a safe and engaging context. Children with a chronic or life-threatening disease may face obstacles that negatively impact play and play development, possibly impeding developmental milestones, beyond the actual illness itself. Currently, there is limited understanding of the impact of (1) aberrant or suppressed play and (2) play-related interventions on the development of chronic diseased children. We argue that stimulating play behaviour enhances the adaptability of a child to a (chronic) stressful condition and promotes cognitive, social, emotional and psychomotor functioning, thereby strengthening the basis for their future health. Systematic play research will help to develop interventions for young patients, to better cope with the negative consequences of their illness and stimulate healthy development.